Candida Infection as an Early Sign of Subsequent Sjögren's Syndrome: A Population-Based Matched Cohort Study - Chen, Chia-Lun; Chang, Fang-Cherng; Hung, Yao-Min; Chou, Mei-Chia; Yip, Hei-Tung; Chang, Renin; Wei, James Cheng-Chung (Frontiers in Medicine, 2022)
Background: Candida infection is prevalent in patients with Sjögren's syndrome (SjS), which usually takes years to reach diagnosis. Is the link a two-way street? The role of Candida infection before SjS has not been examined clearly. This study was conducted to provide epidemiological evidence regarding the relationship between the first acquisition of Candida infection and subsequent SjS. Methods: Totally, 23 494 individuals newly diagnosed with Candida infection were enrolled from 2000, to 2012. Controls (N= 93 976) were selected at a 1:4 ratio through propensity score matched (PSM) using the greedy algorithm. Exposure was defined according to the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes. Main Outcomes and Measures: SjS was recorded in the Registry for Catastrophic Illness Patients Database (RCIPD). Cox proportional hazard model was used to analyze the association and sensitivity analyses for cross-validation. Results: Of 117 470 individuals (106 077 [89%] women), 23 494 individuals (20.0%) had Candida infection and 104 individuals (0.1%) developed SjS. The incidence of SjS was higher in the exposed group compared with the controls (1.92 vs. 0. 98 per 10 000 person-years) with adjusted hazard ratio (aHR) 1.90 (95% CI, 1.25-2.87). The aHRs in subgroups of aged 18 to 30 years, oral candidiasis and depression were 4.30 (95% CI, 1.60-11.55), 4.70 (4.70-13.93) and 6.34 (2.16-18.66). Sensitivity analyses yield consistent results. Conclusions: Residents in Taiwan with Candida infection have higher risk of SjS. For early diagnosis of SjS, clinicians are advised to take Candida infection into account in some situation.